Perbaikan Antarmuka Sistem Informasi WebGIS Potensi Desa (PODES) Badan Pusat Statistik dengan Metode Human Centered Design - Alam Nur Muhammad; Dwija Wisnu Brata; Bondan Sapta Prakoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
The Central Statistics Agency (BPS) is a non-ministerial government agency that is directly responsible to the president and carries out statistical data needs for the government and the public. In developing village potentials based on a survey on the Central Statistics Agency's (BPS) webGIS display design, it was found that there were several problems that needed to be fixed. Problems that have been found such as effectiveness and efficiency in the BPS PODES webGIS design, and color mapping that does not differentiate from one legend to another. Therefore, this research needs to be improved and apply the Human-Centered Design (HCD) approach as a design solution development and use usability testing to determine the value of interface evaluation and user experience. Evaluation of the user interface was carried out twice, namely on the user interface before repairs and after repairs. The first evaluation was carried out for understanding the context of use and validating existing problems. In the first evaluation, which was attended by 5 participants, the average value of effectiveness was 88%, the average efficiency was 0.0251 goals/second and 83.19%, and the satisfaction value based on the SUS score gave a score of 80.125. Meanwhile, for the second evaluation on effectiveness, it got a value of 0.0771 goals/second, for efficiency it got a value of 93% and the SUS score for improving the BPS PODES webGIS interface in the second session was 86.25 and was included in the A+ category (best imaginable) and exceeded the value The SUS percentile is 68 and it shows that the second session of BPS PODES webGIS user interface improvement related to the need for new features already has a high level of satisfaction. New features already have a high level of satisfaction.